2020
DOI: 10.1021/acsnano.0c08296
|View full text |Cite
|
Sign up to set email alerts
|

Self-Winding Helices as Slow-Wave Structures for Sub-Millimeter Traveling-Wave Tubes

Abstract: We present a transformative route to obtain mass-producible helical slow-wave structures for operation in beam−wave interaction devices at THz frequencies. The approach relies on guided self-assembly of conductive nanomembranes. Our work coordinates simulations of cold helices (i.e., helices with no electron beam) and hot helices (i.e., helices that interact with an electron beam). The theoretical study determines electromagnetic fields, current distributions, and beam− wave interaction in a parameter space th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Metal helices obtained by self-assembly of tethered ribbons have potential applications as on-chip transformers [1,2] and inductors, [3,4] microscale actuators, [5] metamaterials, [6] and millimeter-through THz slow-wave structures [7][8][9] for vacuum electronic devices. The diameter and pitch of helical structures required for these diverse applications range from several tens DOI: 10.1002/adfm.202312333 of nanometers to hundreds of micrometers, with the greatest opportunities appearing for robust helices with a micrometer-scale cross-section and pitch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal helices obtained by self-assembly of tethered ribbons have potential applications as on-chip transformers [1,2] and inductors, [3,4] microscale actuators, [5] metamaterials, [6] and millimeter-through THz slow-wave structures [7][8][9] for vacuum electronic devices. The diameter and pitch of helical structures required for these diverse applications range from several tens DOI: 10.1002/adfm.202312333 of nanometers to hundreds of micrometers, with the greatest opportunities appearing for robust helices with a micrometer-scale cross-section and pitch.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising approaches for scalable fabrication of conductive helices rely on the deposition, release, and self-assembly of stressed metal layers patterned into ribbons. [7] The equilibrium diameter of the helical ribbons is determined by the balance of a net bending moment, proportional to the residual stress gradient in the metal heterostructure and internal resistance forces, which are more significant in stiffer metals. [10][11][12] Inherently large stresses in metals would require depositing 0.5-10 μm-thick films to obtain helices with 0-500 μm diameter via self-assembly of stressed metal ribbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent fabrication improvements have also meant helical structures operating at higher frequencies have become possible, e.g. at terahertz frequencies 38 . However, while it has been shown that the frequency bandwidth of slow waves in helical waveguides and antennas is limited 20 , 34 , 35 , there has been no systematic study attempting to characterise, understand and improve upon bandwidth limitations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the planar slow wave structure (SWS) has attracted wide attention over the last decade. One kind of self-winding helix quasi-planar SWS is explored and fabricated by using MEMS technology for potential mass production [10]. The planar SWS features as almost two-dimensional rather than three-dimensional.…”
Section: Introductionmentioning
confidence: 99%